2016
DOI: 10.1088/1361-6528/28/5/054001
|View full text |Cite
|
Sign up to set email alerts
|

Tuning growth direction of catalyst-free InAs(Sb) nanowires with indium droplets

Abstract: The need for indium droplets to initiate self-catalyzed growth of InAs nanowires has been highly debated in the last few years. Here, we report on the use of indium droplets to tune the growth direction of self-catalyzed InAs nanowires. The indium droplets are formed in situ on InAs(Sb) stems. Their position is modified to promote growth in the 〈11-2〉 or equivalent directions. We also show that indium droplets can be used for the fabrication of InSb insertions in InAsSb nanowires. Our results demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…At a critical angle the droplet would slide on to the nanowire sidewall facets. Sliding of the droplet as a result of increasing volume was recently observed by Potts et al [60].…”
Section: Contact Anglementioning
confidence: 63%
“…At a critical angle the droplet would slide on to the nanowire sidewall facets. Sliding of the droplet as a result of increasing volume was recently observed by Potts et al [60].…”
Section: Contact Anglementioning
confidence: 63%
“…The experiments show that, with increasing the annealing time, the droplets increase their volume and move from the NW tip to the side facets, wetting simultaneously two {110} facets. In a related publication, we have shown that these droplets can be further used to nucleate the growth of InAs in a second step in the form of branches perpendicular to the direction of the primary NW [24,42].…”
Section: Experimental Results: Indium Droplets On Inas Nwsmentioning
confidence: 99%
“…Recently, it has been shown that the characteristics of the liquid droplet are essential for many aspect of the growth of the NWs. In particular, it has been shown that the droplet contact angle with the solid NW determines the crystal phase, growth direction, orientation and polarity of the NW itself [8,[22][23][24][25][26]. To that end, we believe that the direct translation of capillarity laws from the planar to the non-planar nanoscale case has not been discussed with enough depth.…”
Section: Introductionmentioning
confidence: 96%
“…InAs nanowires are grown by molecular beam epitaxy (MBE) on GaAs(111)B substrates covered with 4.5 nm of HSQ oxide, as explained in ref 19. Figure 1a,b shows representative top view and cross-sectional scanning electron micrographs (SEM) of samples obtained under typical conditions (530°C, V/III flux ratio of 13.5).…”
Section: ■ Results and Discussionmentioning
confidence: 99%